Potential mechanisms of cancer prevention by weight control - Jiang, Yu; Wang, Weiqun (My University, 2009)
Weight control via dietary caloric restriction and/or physical activity has been demonstrated in animal models for cancer prevention. However, the underlying mechanisms are not fully understood. Body weight loss due to negative energy balance significantly reduces some metabolic growth factors and endocrinal hormones such as IGF-1, leptin, adiponectin, and glucocorticoids, etc., that may be associated with anti-cancer mechanisms. In this review, we summarized the recent studies related to weight control and growth factors. The potential molecular targets focused on those growth factors- and hormones-dependent cellular signaling pathways are further discussed. It appears that multiple factors and multiple signaling cascades, especially for Ras-MAPK-proliferation and PI3K-Akt-anti-apoptosis, could be involved in response to weight change by dietary calorie restriction and/or exercise training. Considering prevalence of obesity or overweight that becomes apparent over the world, understanding the underlying mechanisms among weight control, endocrine change and cancer risk is critically important. Future studies using "-omics" technologies will be warrant for a broader and deeper mechanistic information regarding cancer prevention by weight control.
Keywords: Weight control; Dietary calorie restriction; Physical activity; IGF-1; Leptin; Cancer prevention; Glucocorticoids